Nikolai Zabolotsky and Maria Yudina: On the history of creative communication - Kekova, Svetlana Vasilyevna; Izmajlov, Ruslan Ravilovich (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2023)
The article discusses the history of the creative dialogue between the great pianist Maria Veniaminovna Yudina and the outstanding poet Nikolay Alekseevich Zabolotsky. The material was not only Yudina’s memories of her joint work with the poet on equirhythmic translations of the collection Schubert’s Songs conceived by the pianist, but also Yudina’s thoughts expressed in various sources about the specific features of Zabolotsky’s work, whose poetry Yudina “ardently” loved. Based on Yudina’s definition of the poet’s work as “liturgical”, the article attempts to decipher this characterization. Poem Forest Lake is used for analysis, Yudina having noted that the person who wrote this poem is already on the threshold of the knowledge of God. In connection with the specific features of Zabolotsky’s poetic thought, bordering on the theological understanding of the world and man and embodied in the figurative matter of the Forest Lake, the article interprets the Gospel revelation about man, revealed in the writings of St. Gregorius Dialogus. “Traces” of the creative collaboration between Yudina and Zabolotsky are found in the 1947 poem Beethoven, which is not only the result of the joint work of Yudina and Zabolotsky on equirhythmic translations, but also the verbal embodiment of Yudina’s interpretation of Beethoven’s music, which she often played during their meetings with Zabolotsky. The article shows the specific character of the creative method of typological exegesis (this term is introduced by L. Levshun for the study of ancient Russian literature), which is used by Zabolotsky in the poems Forest Lake and Beethoven. Its essence lies in the fact that for any phenomenon or event a prototype is found in the Holy Scriptures and, thus, the event is explained, interpreted within the framework of the biblical paradigm. Zabolotsky does not interpret anything, but directs the reader’s feeling to unravel what kind of sacrament occurs in his poetry. Nikolay Zabolotsky in the poem Beethoven embodied Maria Yudina’s idea about music being a “message of revealed truths”, about music, which is the realization of the universal, cosmic liturgy.